Structural Elucidation Studied on Transition Metal Complexes of New Hydrazino Quinoxaline Derivatives - Ananthalakshmi, P.V.; Sandhyarani, D.; Jayatyagaraju, V. (Asian Journal of Chemistry, 2010)
Cr(III), Mn(II), Fe(III), Co(II) , Ni(II) and Cu(II) complexes of new tridentate oxygen-nitrogen donors, N-salicylidene-3-hydrazino quinoxalin- 2-one (HSHQO) and N-(2-hydroxy)-acetophenonyl 3-hydrazinoquinoxalin-2-one (HHAHQO), have been prepared and characterized by elemental analysis, conductance, thermal, spectral and magnetic data. HSHQO acts as a monobasic tridentate ONN donor through the phenolic oxygen and azomethine nitrogens where as HHAHQO acts as a monobasic ONO donor through the phenolic oxygen, azomethine (free) nitrogen and carbonyl oxygen in all the complexes.